Association of Vitamin K Insufficiency as Evaluated by Serum Undercarboxylated Osteocalcin With Frailty in Community-Dwelling Older Adults - Azuma, Kotaro; Osuka, Yosuke; Kojima, Narumi; Sasai, Hiroyuki; Kim, Hunkyung; Inoue, Satoshi (Frontiers in Aging, 2022)
Frailty is a state of reduced ability to recover from stress. Intervention to frailty is important for fulfilling healthy longevity. Vitamin K is a fat-soluble vitamin contained in vegetables and fermented food. Although vitamin K is shown to be associated with several age-related diseases, studies on association of vitamin K intake and frailty in older population are limited. In the present study, a total of 800 community-dwelling older adults (mean age = 75.9) were recruited for comprehensive geriatric health examination including frailty evaluation based on Japanese version of the Cardiovascular Health Study criteria. Serum concentration of total osteocalcin (OC) and undercarboxylated osteocalcin (ucOC) were measured. The ratio of ucOC and OC (ucOC/OC) which reflects vitamin K insufficiency was calculated for each participant, and the values were divided into quartiles. Binary logistic regression analysis was performed to evaluate the risk of frailty for each quartile of ucOC/OC with the lowest quartile as the reference. Significant association of frailty and highest quartile of ucOC/OC was found with the odds ratio of 2.49 (P = 0.023) with adjustment with age, sex, body mass index, dietary intake, and several clinical characteristics. When the analysis was repeated in each component of frailty, the highest quartiles of ucOC/OC had tendency of association with ‘slow walking speed’ and ‘low activity’. Our findings demonstrated the association between vitamin K insufficiency and frailty in older population. Our analysis also suggests that vitamin K insufficiency could be associated with selected components of frailty.